1995
DOI: 10.1093/jpepsy/20.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Sibling Adaptation To Childhood Cancer Collaborative Study: Siblings' Perceptions Of The Cancer Experience

Abstract: Investigated responses of siblings (N = 254) of children with cancer to structured interviews designed to elicit thoughts and feelings about effects of cancer on self and family. Siblings indicated distress about family separations and disruptions, lack of attention, focus of family on the ill child, negative feelings in themselves and family members, cancer treatments and their effects, and fear of death. Siblings also reported becoming more compassionate, families becoming closer, and having experiences they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(115 citation statements)
references
References 0 publications
5
107
1
2
Order By: Relevance
“…Whereas Sargent et al 38 reported that families and professionals may be becoming more skilled at informing siblings about cancer and its treatment, the siblings in our study reported lack of information about BMT. Siblings require age-related information and preparation.…”
Section: Future Researchcontrasting
confidence: 76%
“…Whereas Sargent et al 38 reported that families and professionals may be becoming more skilled at informing siblings about cancer and its treatment, the siblings in our study reported lack of information about BMT. Siblings require age-related information and preparation.…”
Section: Future Researchcontrasting
confidence: 76%
“…Researchers who investigated the outcomes of individuals who had siblings that were diagnosed with cancer in childhood have primarily focused on short-term psychological outcomes in children and adolescents (e.g. Chesler, Allswede, & Barbarin, 1991;Gogan, Koocher, Foster, & O'Malley, 1977;Gogan & Slavin, 1981;Nolbris, Enskär, & Hellström, 2007;Sargent et al, 1995;Woodgate, 2006). Very little attention was on the long-term effects of childhood cancer on siblings or adults whose siblings had cancer during childhood.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Furthermore, healthy siblings are at risk for psychological issues due to the stress and challenges associated with having a sibling with cancer (Chesler et al, 1991;Gogan & Slavin, 1981;Sargent et al, 1995). There is a need for new interventions for adult healthy siblings and for more in-depth information about the long-term effects of having a sibling with cancer.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 2 more Smart Citations